Photocatalytic degradation of ofloxacin by perovskite-type NaNbO3 nanorods modified g-C3N4 heterojunction under simulated solar light: Theoretical calculation, ofloxacin degradation pathways and toxicity evolution - Dandan Zhang; Juanjuan Qi; Ji, Haodong; Si Li; Long Chen; Taobo Huang; Chaokai Xu; Xingmin Chen; Liu, Wen (Chemical Engineering Journal, 2020)
Graphitic carbon nitride (g-C3N4) is widely used as a visible-light-driven photocatalyst but limited by the rapid photoexcited electron-hole pairs recombination rate. To promote the photocatalytic activity of g-C3N4, a class of heterojunction photocatalysts, perovskite-type sodium niobate (NaNbO3) nanorods modified g-C3N4 (SNCN), was fabricated through a two-step hydrothermal and thermal polymerization method in this study. X-ray powder diffraction (XRD), transmission electron microscope (TEM) and X-ray photoelectron spectroscopy (XPS) demonstrated the successful decoration of NaNbO3 onto g-C3N4, as well as the formation of material interface with high reactivity. The optimal material (SNCN-3) exhibited an extremely high degradation efficiency of ofloxacin (OFL) under simulated solar light, as the kinetic rate constant (k) was 29.6 and 10.4 times of that for the neat g-C3N4 and NaNbO3, respectively. Energy band structure analysis indicated that SNCN-3 was a type II heterojunction. Moreover, surface photovoltage (SPV), photoluminescence (PL) and transient photocurrent response measurements confirmed SNCN-3 had the highest electron-hole separation efficiency compared with NaNbO3, g-C3N4 and the other SNCN composites. Quenching tests indicated that O2– and holes were the primary reactive species for OFL degradation. Density functional theory (DFT) calculation on further revealed the atoms of OFL with high Fukui index (f 0) preferred to be attacked by the produced radicals. Cleavage of piperazine moiety and substitution of F were the key OFL degradation pathways. In addition, the reduced toxicity of transformation products after photocatalysis verified the proposed technique was a green method. This work provided the promising application of g-C3N4/NaNbO3 heterojunction photocatalysts for degradation of antibiotic pollutants in water.
Keywords: Carbon nitride; Heterojunction; Photocatalysis; Sodium niobate; Theoretical calculation